Cohort study of pain symptoms and management following impacted mandibular third molar extraction. (26th September 2016) - Motonobu, A; Hidemichi, Y; Eri, U; Takashi, T; Kenichi, K
Abstract : Objective: The aim of this study was to investigate the possibility of intravenous sedation as a useful pain‐relieving option for impacted third molar extractions. Subjects and methods: A prospective cohort study was conducted among patients who underwent bilateral mandibular third molar extractions under local anaesthesia and intravenous sedation (sedation group) and patients who underwent unilateral mandibular third molar extraction under local anaesthesia alone (local anaesthesia group). The frequency of use of postoperative oral analgesia and the intensity of pain assessed using the full cup test were compared between the two groups. Results: The maximum pain intensity (0–100) on postoperative day 1 in the sedation and local anaesthesia groups was 72.8 ± 16.98 and 84.8 ± 15.84, respectively, and the mean pain intensity was 42.2 ± 16.00 and 49.6 ± 18.94. The maximum and mean pain intensities in the sedation group were significantly milder than those in the local anaesthesia group. The number of oral analgesic doses in the sedation group was significantly smaller on the day of surgery and on postoperative day 1 than in the local anaesthesia group. Conclusions: The results of this study suggest that bilateral impacted mandibular third molar extractions under intravenous sedation could be a recommended treatment option.